2021
DOI: 10.1002/adom.202100526
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Luminescence from Stable Silver Nanoclusters Confined in Microporous Zeolites

Abstract: properties associated with nanoclusters' molecule-like structure and energetics. Most notably, metal nanoclusters rose to research prominence in connection to the discovery of outstanding optoelectronic properties and have found practical application within catalysis, bioimaging, lighting and molecular sensing. [1][2][3][4][5][6] However, nanocluster' stabilization remains a significant impediment owing to their tendency to merge and form ever-larger aggregates at the loss of their interesting properties. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 62 publications
0
26
0
Order By: Relevance
“…, discrete energy levels). 1–9 Nevertheless, there is a strong tendency for silver nanoclusters to aggregate into large non-fluorescent species, limiting their applications. 10–12 Zeolites have a specific pore-cage structure and facile ion exchange capability, and thus they can be used as desirable scaffolds to stabilize nanoclusters.…”
Section: Introductionmentioning
confidence: 99%
“…, discrete energy levels). 1–9 Nevertheless, there is a strong tendency for silver nanoclusters to aggregate into large non-fluorescent species, limiting their applications. 10–12 Zeolites have a specific pore-cage structure and facile ion exchange capability, and thus they can be used as desirable scaffolds to stabilize nanoclusters.…”
Section: Introductionmentioning
confidence: 99%
“…AgNCs with tunable emission properties can be prepared using bioactive peptides in an aqueous medium . Romolini et al reported tunable luminescence from stable AgNCs confined in microporous zeolites . The synthesis of AgNCs embedded zein films as antimicrobial coating materials for food packaging has been reported .…”
Section: Introductionmentioning
confidence: 99%
“…28 Romolini et al reported tunable luminescence from stable AgNCs confined in microporous zeolites. 29 The synthesis of AgNCs embedded zein films as antimicrobial coating materials for food packaging has been reported. 30 Jin and co-workers synthesized Ag 7 NCs with high yield by the reduction of AgNO 3 using meso-2,3-dimercaptosuccinic acid (DMSA) ligands.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The nanoclusters consisting of only a few atoms or ions possess a discrete molecule-like energy band and thus show size-dependent luminescence performance. In the recent years, Ag NCs with different sizes, topologies, and chemical states have attracted much research interest due to their pronounced optical properties like high quantum yield approaching that of commercial phosphors and tunable emission in the visible region, which open up new vistas in potential photocatalytic, imaging, detection, and illumination applications. However, Ag NCs undergo aggregation easily due to their high surface energy and thus lose their radiative emission ability. ,, In order to spatially and chemically stabilize Ag NCs and obtain the desired optical properties, two types of scaffolds were generally applied during the synthesis process: (1) soft organic molecules like DNA, peptides, and polymers, and (2) a rigid inorganic matrix including glasses and zeolites, whereby the few-atom size clusters can be stabilized by immobility. …”
Section: Introductionmentioning
confidence: 99%
“…1−4 However, Ag NCs undergo aggregation easily due to their high surface energy and thus lose their radiative emission ability. 1,5,6 In order to spatially and chemically stabilize Ag NCs and obtain the desired optical properties, two types of scaffolds were generally applied during the synthesis process: (1) soft organic molecules like DNA, peptides, and polymers, and (2) a rigid inorganic matrix including glasses and zeolites, whereby the few-atom size clusters can be stabilized by immobility. 7−10 Zeolites are microporous crystalline aluminosilicates constituted by a framework of interconnected TO 4 tetrahedra (T = Si or Al) with a tailored structure and varied extra-framework cations.…”
Section: Introductionmentioning
confidence: 99%